KITABUTTURAS LEARNING SYSTEM AT BAITUSSABRI SALAFI DAYAH LAMBRO DEYAH VILLAGE, SUB DISTRICT KUTA BARO ACEH BESAR DISTRICT - Hadi, Abdul; Miswar, Miswar; Hasymi, M. Ali (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The Kitabutturas learning system at Dayah Salafi Baitussabri is running well thanks to strong support from the quality of the teachers, the motivation of the students, and the religious environment of the Islamic boarding school. However, there are several obstacles that need to be overcome, such as language difficulty, limited facilities, and differences in the educational background of the students. The method in this research is to use qualitative research with a field research approach. The results of the study showed that 1). The Kitabutturas learning system applied at Dayah Salafi Baitussabri, Lambro Deyah Village, Kuta Baro Sub District, Aceh Besar District is implemented through the traditional bandongan and sorogan methods, which are effective in teaching in-depth understanding of various Islamic disciplines, such as fiqh, tauhid, and tasawuf. Learning takes place intensively every day with a tight schedule. Although this method is successful in improving students' understanding of religion, the challenges faced include difficulty in understanding classical Arabic and limited facilities that support the learning process. 2). Supporting and inhibiting factors in the Kitabutturas learning system at Dayah Salafi Baitussabri, Lambro Deyah Village, Kuta Baro Sub District, Aceh Besar District are supporting factors in the Kitabutturas learning system at Dayah Salafi Baitussabri include the quality and commitment of teachers, motivation and discipline of students, and a religious pesantren environment. The bandongan and sorogan methods have proven effective in guiding students to understand religious texts. However, the challenges faced include difficulties in understanding classical Arabic, limited educational facilities, and differences in the educational backgrounds of the students. Despite these obstacles, the strong commitment of the teachers and students ensures that the learning process continues to run well.